Pharmaceutical Entrepreneurs - Wahyu Toha Abdul Hak; Rifqoh Fauziyah (Walidem Institute and Publishing, 2026)
Objective: This study aims to understand the definition of entrepreneurship, the characteristics of good entrepreneurs, and the types of entrepreneurs in the pharmaceutical sector. Theoretical framework: The theoretical framework of this research is based on the concept of entrepreneurship as the ability of individuals to recognize, manage, and develop their potential optimally to create added value and improve their standard of living. In the pharmaceutical sector, entrepreneurship is associated with innovation and managerial ability. Literature review: A literature review discusses the definition of entrepreneurship from various perspectives and characteristics of entrepreneurs, such as creativity, innovation, leadership, and decision-making ability. In addition, entrepreneurial opportunities in the pharmaceutical sector were also discussed. Method: Research using the systematic review method with the PRISMA approach. Articles are searched using the keyword